2017
DOI: 10.3389/fmicb.2017.01765
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Beneficial Microbes: The Case of Akkermansia muciniphila

Abstract: Metabolic disorders associated with obesity and cardiometabolic disorders are worldwide epidemic. Among the different environmental factors, the gut microbiota is now considered as a key player interfering with energy metabolism and host susceptibility to several non-communicable diseases. Among the next-generation beneficial microbes that have been identified, Akkermansia muciniphila is a promising candidate. Indeed, A. muciniphila is inversely associated with obesity, diabetes, cardiometabolic diseases and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
546
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(578 citation statements)
references
References 73 publications
23
546
2
7
Order By: Relevance
“…Verrucomicrobia is also increased in abundance in dextran sodium sulphate-induced murine colitis [62]. On the other hand, evidence indicates that the species Akkermansia muciniphila of the Verrucomicrobia phylum has a protective anti-inflammatory effect against specific metabolic disorders and obesity [63]. …”
Section: Discussionmentioning
confidence: 99%
“…Verrucomicrobia is also increased in abundance in dextran sodium sulphate-induced murine colitis [62]. On the other hand, evidence indicates that the species Akkermansia muciniphila of the Verrucomicrobia phylum has a protective anti-inflammatory effect against specific metabolic disorders and obesity [63]. …”
Section: Discussionmentioning
confidence: 99%
“…The administration of Akkermansia muciniphila can ameliorate metabolic symptoms of obesity, diabetes, and alcoholic liver disease in mice (Everard et al 2013, Grander et al 2017. The beneficial effect of this bacterium could also be conferred by administrating pasteurised bacteria and an immuno-stimulatory outer membrane protein (Amuc_1100) in mice (Cani and de Vos 2017, Ottman et al 2017b, Plovier et al 2017. The mode of health-promoting mechanisms include the increase of mucus thickness and gut barrier function (Everard et al 2013), direct host immune stimulation (Ottman et al 2017b), and stimulation of a beneficial mucosal community (Chapter 4 and 5) .…”
Section: Novel Probiotic Strainsmentioning
confidence: 99%
“…Akkermansia muciniphila, Bacteroides spp. and short-chain fatty acids (SCFAs)-producing bacteria are promising candidates (Cani & de Vos, 2017;Tan et al, 2019;Rivière, Selak, Lantin, Leroy, & De Vuyst, 2016). It was reported that A. muciniphila improved metabolic disorders associated with obesity, diabetes, liver diseases, and cardiometabolic disorders (Cani & de Vos, 2017).…”
Section: Overvie W Of Prob I Oti C Smentioning
confidence: 99%